Standardization of Terms and Definitions in Computer Forensic Science - N. A. Khatuntsev (Теория и практика судебной экспертизы, 2017)
The current situation with the use of terms and definitions in the practice of computer forensics is examined. The author argues for the need to develop and issue a dedicated national standard: GOST R 5742902017 «Computer Forensic Science. Terms and Definitions». Problems with the drafting of the GOST are discussed, and pathways for further development of the computer forensics concept base are mapped out